Analisis Dampak Deflasi Terhadap Kesejahteraan Masyarakat Palembang dalam Tinjauan Ekonomi Islam - Rolis; Maya Panorama (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The deflation phenomenon that occurred in Palembang City for four consecutive months from April to July 2023 had a significant impact on the local economy, such as weakened purchasing power, increased unemployment, and decreased income for business actors, especially MSMEs. This study aims to analyze the impact of deflation on the welfare of the people of Palembang from the perspective of Islamic economics, emphasizing the values of justice (‘adl), public interest (maslahah), and balance (tawazun). The research method used is descriptive qualitative through literature review and content analysis of various secondary sources, including data from the Central Statistics Agency (BPS), scientific journals, and Islamic economic perspectives. The results show that deflation not only affects the economy but also causes social inequality that contradicts Islamic principles. To address this, policies based on Islamic values are needed, such as optimizing the distribution of zakat and infaq, productive economic training programs, and monetary policies that support justice and welfare. Thus, the Islamic economic approach is considered capable of providing a more holistic solution in facing the challenges of deflation at the local level.